Dermatosis neglecta - Elisa Mayumi Kubo Sasaya; Carolina Ghislandi; Flávia Trevisan; Talita Beithum Ribeiro; Fabiane Mulinari-Brenner; Caroline Balvedi Gaiewski (Sociedade Brasileira de Dermatologia, 2015)
AbstractDermatosis neglecta is the name of a skin condition characterized by papules and polygonal plaques, which are sometimes warty, brownish and hyperpigmented, adherent and symmetric, though removable with ethyl or isopropyl alcohol. It occurs due to inadequate skin cleansing causing accumulation of sebum, sweat, keratin and impurities. Its occurrence, though little reported, is frequent. The main differential diagnosis is the Terra fi rma-forme dermatosis. The treatment is simple, with exfoliation, moisturizing and even rubbing of alcohol. Causes of negligence on the patient's side, which can range from hygiene carelessness to psychiatric disorders, local hypersensitivity, limbs negligence or motor paralysis, should be investigated. We illustrate the case of dermatosis neglecta in a 45-years old patient admitted with pulmonary sepsis.